Evolution of thermo-mechanical properties of concrete with calcium aluminate cement and special aggregates for energy storage - Roig-Flores, Marta (2021)
With the ever-expanding presence of solar energy, the design of cost-efficient heat energy storage systems is becoming increasingly relevant. Concrete is a potential solid material for these systems but raises questions of its response at high temperatures in operating conditions. This work studies concrete designed with calcium aluminate cement and three types of aggregates that are stable at high temperatures. The designed concrete mixes were exposed to thermal cycles (290–550 ◦C), and their thermal fatigue response was evaluated with mechanical, cracking, thermal, and microstructural analyses at room temperature after heat cycles. The obtained results show that the main changes are mostly produced after the first thermal cycle and are stabilized during successive thermal cycles, with only a slight decrease in the thermo-mechanical properties. The results showed stabilization of cracking, crack widths between 10 and 80 μm, reduction of compressive strength, around 50–65%, and reduction of the thermal conductivity by 30%